Arctic zircon U-Pb ages reveal multiphase glaciations in East Siberia during the late Quaternary - Han Feng; Zhengquan Yao; Xuefa Shi; Zhongshi Zhang; Huayu Lu; Hanzhi Zhang; Yanguang Liu; Xin Shan; Jiang Dong; Linsen Dong; Gongxu Yang; Limin Hu; et al. (Nature Communications)
Abstract Tracing ice-rafted debris (IRD) in Arctic Ocean sediments is crucial for understanding the evolution of Northern Hemisphere ice cover. However, uncertainties in identifying the provenance of IRD across circum-Arctic shelves have complicated reconstructions of the East Siberian Ice Sheet (ESIS). Here, we present a provenance study using 10,111 detrital zircon U-Pb ages from circum-Arctic shelf sediments and central Arctic IRD. Our results reveal that a prominent ~90–110 Ma zircon peak serves as a distinctive fingerprint for East Siberian-sourced sediments. Central Arctic IRD from at least four glacial periods contains this signature, indicating repeated ESIS glaciation, likely within the past three glacial cycles. This multiphase glaciation of East Siberia exerted significant, though poorly understood, influences on both polar and global climates during the late Quaternary. Our findings provide valuable insights into the history of Northern Hemisphere glaciation and offer an effective approach for reconstructing ice sheet evolution.